2014
DOI: 10.1111/ppa.12245
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of ‘Candidatus Liberibacter solanacearum’ in carrot seeds

Abstract: A protocol for the specific detection and quantification of ‘Candidatus Liberibacter solanacearum’ in carrot seeds using real‐time PCR was developed. The bacterium was detected in 23 out of 54 carrot seed lots from 2010 to 2014, including seeds collected from diseased mother plants. The average total number of ‘Ca. L. solanacearum’ cells in individual seeds ranged from 4·8 ± 3·3 to 210 ± 6·7 cells per seed from three seed lots, but using propidium monoazide to target live cells, 95% of the cells in one seed lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(88 citation statements)
references
References 34 publications
(66 reference statements)
0
83
2
3
Order By: Relevance
“…Consequently, a lower prevalence of symptoms in celery was observed, whereas the presence of symptomatic carrots was similar to the previous years. This was likely, due to the primary infection caused by carrot seed transmission that was recently demonstrated (Bertolini et al, 2015). In both of the surveyed years, the arthropods collected on sticky celery plants showed the same psyllid species structure: B. trigonica was always the prevalent species and B. nigricornis was the less frequently observed species, with only two caught specimens in 2011.…”
Section: A) B) C)mentioning
confidence: 81%
See 2 more Smart Citations
“…Consequently, a lower prevalence of symptoms in celery was observed, whereas the presence of symptomatic carrots was similar to the previous years. This was likely, due to the primary infection caused by carrot seed transmission that was recently demonstrated (Bertolini et al, 2015). In both of the surveyed years, the arthropods collected on sticky celery plants showed the same psyllid species structure: B. trigonica was always the prevalent species and B. nigricornis was the less frequently observed species, with only two caught specimens in 2011.…”
Section: A) B) C)mentioning
confidence: 81%
“…For this reason, we focused our interest in psyllid species. Bertolini et al (2015) reported that the presence of B. trigonica and other species was correlated with an increase in the prevalence of the bacterium from 2% to approximately 100% after six months of carrot cultivation. Other experiences with emerging diseases in the citrus and potato industries suggest that psyllid species, feeding briefly outside their normal plant host range, could introduce a pathogen to another crop (Nelson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, Lso has caused severe economic losses to the fresh carrot market in Norway, Finland, Germany and Spain. These losses can lead to important decrease in marketable yield (Munyaneza et al, 2010a;Laska, 2011;Teresani et al, 2014;Bertolini et al, 2015). Five haplotypes of Lso have been described so far.…”
Section: The Pathogen Candidatus Liberibacter Solanacearummentioning
confidence: 99%
“…Psyllids transmit several phloem restricted bacteria such as phytoplasmas and different species of the genus Candidatus Liberibacter (Bové and Garnier, 2003;Munyaneza, 2010;Trivedi et al, 2016). Among the Candidatus Liberibacter species, found in Europe, Candidatus Liberibacter solanacearum (Lso) is considered one of the most important ones due to the serious losses it cause to the carrot and celery industries (Munyaneza et al, 2010a;Bertolini et al, 2015). In Europe, two carrot psyllid species have been reported as vectors of Lso, Bactericera trigonica Hodkinson and Trioza apicalis Foester (Munyaneza et al, 2010a,b;Alfaro-Fernández et al, 2012b;).…”
Section: Psyllids As Agricultural Pestsmentioning
confidence: 99%